SP0172 Glucocorticoids: Still a threat to bone?. (23rd January 2014) - Compston, J.
Abstract : Osteoporosis is a common complication of oral glucocorticoid therapy and is associated with significant morbidity. Glucocorticoid-induced osteoporosis is characterised by rapid bone loss and increased fracture risk during the first few months of therapy. The increase in fracture risk is dose-related and is most prominent in the spine. Although awareness of glucocorticoid-induced osteoporosis has increased in recent years, the condition remains under-treated. Recently there have been advances in fracture risk assessment and treatment in glucocorticoid-induced osteoporosis. The fracture risk algorithm FRAX® includes glucocorticoid use as a risk factor but does not take account of the dose, thus underestimating fracture risk in individuals taking higher doses. A modification to FRAX has recently been developed that provides an adjustment for the dose of glucocorticoids. A range of pharmacological interventions is now available for the management of glucocorticoid-induced osteoporosis, including oral and intravenous bisphosphonates and the anabolic agent, teriparatide. New recommendations incorporating these advances have recently been issued by the American College of Rheumatology and a joint working group from the International Osteoporosis Foundation and the European Calcified Tissue Society. Disclosure of Interest: None Declared